Nonalcoholic fatty liver disease in women with polycystic ovary syndrome - Paschou, Stavroula A.; Polyzos, Stergios A.; Anagnostis, Panagiotis; Goulis, Dimitrios G.; Kanaka-Gantenbein, Christina; Lambrinoudaki, Irene; Georgopoulos, Neoklis A.; Vryonidou, Andromachi (Endocrine, 2020)
Polycystic ovary syndrome (PCOS) affects 6–15% of women of reproductive age. Nonalcoholic fatty liver disease (NAFLD) affects 25–30% of the general population and its prevalence increases in parallel with the epidemics of obesity and type 2 diabetes mellitus. A growing body of evidence suggests that NAFLD and PCOS quite often co-exist. The aim of this article is to summarize and critically appraise the literature regarding: (1) the rates of co-existence of the two entities, (2) the possible pathophysiological links, (3) the proper diagnostic assessment and (4) the appropriate management of women with NAFLD and PCOS. Data from clinical studies and meta-analyses indicate a higher prevalence of NAFLD in women with PCOS ranging from 34% to 70% compared with 14% to 34% in healthy women. Inversely, women with NAFLD are more often diagnosed with PCOS. Insulin resistance (IR) and hyperandrogenism are two main potential pathophysiological links between the two entities. In this regard, IR seems to interplay with obesity and hyperandrogenism, thus affecting NAFLD and PCOS and being affected by them. Women with PCOS, particularly those with IR and/or hyperandrogenism, are suggested to be screened for NAFLD, while premenopausal women with NAFLD is suggested to be screened for PCOS. Lifestyle recommendations with a change in dietary habits, weight loss and exercise, constitute currently the cornerstone of the management of both NAFLD and PCOS. Insulin sensitizers maybe used for the treatment of these women, while there are limited promising data for the use of liraglutide.